Inhibition of tumor‐associated macrophages by trabectedin improves the antitumor adaptive immunity in response to anti‐PD‐1 therapy. Issue 11 (8th October 2021) - Belgiovine, Cristina; Frapolli, Roberta; Liguori, Manuela; Digifico, Elisabeth; Colombo, Federico Simone; Meroni, Marina; Allavena, Paola; D'Incalci, Maurizio
Abstract: A considerable proportion of cancer patients are resistant or only partially responsive to immune checkpoint blockade immunotherapy. Tumor‐Associated Macrophages (TAMs) infiltrating the tumor stroma suppress the adaptive immune responses and, hence, promote tumor immune evasion. Depletion of TAMs or modulation of their protumoral functions is actively pursued, with the purpose of relieving this state of immunesuppression. We previously reported that trabectedin, a registered antitumor compound, selectively reduces monocytes and TAMs in treated tumors. However, its putative effects on the adaptive immunity are still unclear. In this study, we investigated whether treatment of tumor‐bearing mice with trabectedin modulates the presence and functional activity of T‐lymphocytes. In treated tumors, there was a significant upregulation of T cell‐associated genes, including CD3, CD8, perforin, granzyme B, and IFN‐responsive genes (MX1, CXCL10, and PD‐1), indicating that T lymphocytes were activated after treatment. Notably, the mRNA levels of the Pdcd1 gene, coding for PD‐1, were strongly increased. Using a fibrosarcoma model poorly responsive to PD‐1‐immunotherapy, treatment with trabectedin prior to anti‐PD‐1 resulted in improved antitumor efficacy. In conclusion, pretreatment with trabectedin enhances the therapeutic response to checkpoint inhibitor‐based immunotherapy. These findings provide a good rational for the combination of trabectedin with immunotherapy regimens. Abstract : Trabectedin selectively reduces Tumor‐Associated Macrophages (TAMs) and increases the number of CD8+ lymphocytes and their expression of PD‐1, perforin, and granzyme B in treated tumors. Treatment with anti‐PD‐1, following trabectedin administration, unleashes adaptive immune responses and results in improved antitumor efficacy.